2022
DOI: 10.1007/s13555-022-00845-4
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia Areata in Latin America: Where are We and Where are We Going?

Abstract: Alopecia areata (AA) represents an underrecognized burden in Latin America (LA), severely impacting quality of life (QoL). This impact is exacerbated by limited access to specialized dermatologic care and therapies for AA within and among nations. Many of the unmet needs for AA globally also exist in LA. The region has geographic, ethnic, cultural, and economic conditions. With new AA medicines targeting immunologic pathways on the horizon, LA must prepare regarding regulatory issues, reimbursement, awareness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In more severe instances, alopecia may affect the entire scalp or body, known as alopecia totalis (AT) or alopecia universalis (AU) 1 . The prevalence of AA worldwide varies from 0.57% to 3.8% among the general population 3 . Research has suggested that AA arises from an autoimmune attack on hair follicles (HFs), and the loss of immune privilege (IP) within the anagen hair bulb serves as a crucial precursor to the development of AA 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In more severe instances, alopecia may affect the entire scalp or body, known as alopecia totalis (AT) or alopecia universalis (AU) 1 . The prevalence of AA worldwide varies from 0.57% to 3.8% among the general population 3 . Research has suggested that AA arises from an autoimmune attack on hair follicles (HFs), and the loss of immune privilege (IP) within the anagen hair bulb serves as a crucial precursor to the development of AA 4 .…”
Section: Introductionmentioning
confidence: 99%
“…1 The prevalence of AA worldwide varies from 0.57% to 3.8% among the general population. 3 Research has suggested that AA arises from an autoimmune attack on hair follicles (HFs), and the loss of immune privilege (IP) within the anagen hair bulb serves as a crucial precursor to the development of AA. 4 CD8+ lymphocytes are responsible for follicular damage primarily and dominate the disease activation process, with CD4+ lymphocytes playing an auxiliary role.…”
mentioning
confidence: 99%